Tingkat Pengetahuan Dan Penggunaan Jamu Di Desa Jawa Laut Kota Martapura: Studi Cross-Sectional - Fitriah, Rahmayanti; Sihombing, Yuliana; Wahyudi, Wahyudi (JURNAL FARMASI GALENIKA, 2025)
Herbal medicine is one form of traditional medicine that is still widely used by the Indonesian people. The perception that herbal medicine is safer than modern medicine is one of the reasons for the high demand for its use. However, the trend of increasing consumption of herbal medicine among the public has brought new challenges, particularly regarding safety, quality, and efficacy claims. Without adequate knowledge, the use of jamu carries the risk of side effects, interactions with modern medications, or improper dosing. Therefore, a good understanding of the proper and safe use of jamu is crucial to prevent potential hazards and ensure optimal benefits. The objective of this study is to investigate the relationship between knowledge levels and jamu use in Jawa Laut Village, Martapura City. This study employed an analytical observational method with a cross-sectional approach using non-random sampling, specifically accidental sampling, conducted from January to March 2022. In this study, univariate and bivariate data were analyzed using the Chi-Square test. The results showed that the community's knowledge was in the good category, with 79 respondents (79%), and herbal medicine use was in the high category, with 76 respondents (76%). Thus, there is a relationship between knowledge and herbal medicine use in Jawa Laut Village, Martapura City, South Kalimantan, Indonesia.